Nanopyramid copper structures on screen-printed carbon electrode for high-performance non-enzymatic glucose sensing: A cost-effective and scalable approach - Sahar Bakhshi; Mahsa Rahmanipour; Amir R. Amirsoleimani; Mostafa Rezazadeh; Hossein Siampour; Ahmad Moshaii (Sensing and Bio-Sensing Research, 2024)
We report on the fabrication of a robust non-enzymatic glucose sensor featuring a sensing electrode composed of pyramid-shaped copper/copper oxide (Cu/Cu2O) nanostructures formed through a simple electrodeposition process on a screen-printed carbon electrode (SPCE). The fabrication of Cu/Cu2O nanostructures on the SPCE enhances the charge transfer and electrocatalytic performance of the sensor, proving advantageous for glucose sensing. Notably, this morphology contributes to electrochemical glucose determination over a wide linear range of 0.01 to 6 mM, with a sensitivity of 214.04 μA/(mM·cm2) and a low detection limit of 0.03 μM. The proposed simple approach ensures high reproducibility, stable attachment to the printed layer, and cost-effectiveness, making it well-suited for scalable production of non-enzymatic glucose sensors.